Development of Accurate BSIM4 Noise Parameters for CMOS 0.13-µm Transistors in Below 3-GHz LNA Application - Asmaa Nur Aqilah Zainal Badri; Norlaili Mohd Noh; Shukri bin Korakkottil Kunhi Mohd; Asrulnizam Abd Manaf; Arjuna Marzuki; Mohd Tafir Mustaffa; Mohamed Fauzi Packeer Mohamed (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Accurate transistor thermal noise model is crucial in IC design as it allows accurate selection of transistors for specific frequency application. The accuracy of the model is represented by the similarity between the simulated and the measured noise parameters (NPs). This work was based on a problem faced by a foundry concerning the dissimilarities between the measured and simulated NPs, especially minimum noise figure (NFmin) for frequencies below 3 GHz.